2018
DOI: 10.5114/aic.2018.79869
|View full text |Cite
|
Sign up to set email alerts
|

CHA2DS2-VASc and R2-CHA2DS2-VASc scores predict in-hospital and post-discharge outcome in patients with myocardial infarction

Abstract: IntroductionThe CHA2DS2-VASc and R2-CHA2DS2-VASc scores were initially designed to evaluate the risk of cerebrovascular events in patients with atrial fibrillation. However, these scales consist of parameters which are well known as general risk factors for cardiovascular events.AimTo assess the role of the CHA2DS2-VASc and R2-CHA2DS2-VASc scores in predicting outcome of patients with myocardial infarction (MI).Material and methodsWe enrolled 212 consecutive patients with both ST-elevation and non-ST-elevation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In the same way, R2CHA2DS2VASc score awards an additional 2 points for CrCl < 60 mL/min and GFR < 60 mL/min/1.73 m 2 and has already been used to predict long-term outcomes for patients with coronary artery disease (CAD)20 and acute coronary syndromes (ACS) [ 20 22 ].…”
Section: Chads2 Cha2ds2-vasc R2chads2 and R2cha2ds2vasc Scoresmentioning
confidence: 99%
“…In the same way, R2CHA2DS2VASc score awards an additional 2 points for CrCl < 60 mL/min and GFR < 60 mL/min/1.73 m 2 and has already been used to predict long-term outcomes for patients with coronary artery disease (CAD)20 and acute coronary syndromes (ACS) [ 20 22 ].…”
Section: Chads2 Cha2ds2-vasc R2chads2 and R2cha2ds2vasc Scoresmentioning
confidence: 99%
“…It follows that several studies showed that higher scores correlated with the presence or severity of coronary artery disease (CAD), contrast-induced nephropathy after percutaneous coronary intervention (PCI), no-reflow phenomenon in patients with acute myocardial infarction (AMI), in-stent restenosis, acute stent thrombosis after acute coronary syndrome and cardiovascular prognosis. [4][5][6][7][8][9] Recently, a new score, CHA2DS2-VASc-HSF, was developed by adding smoking, hyperlipidemia, and family history of CAD to the CHA2DS2-VASc score; in addition, the female gender was replaced by the male gender. 10 Recent studies reported that this new score showed better performance compared with the CHADS2 and CHA2DS2-VASc scores in evaluating CAD.…”
Section: Dear Editormentioning
confidence: 99%
“…The components of these two scores are associated with atherosclerosis, vascular spasm, and microvascular dysfunction, which overlap the risk factors of NRP [7]. Several recent studies have also shown that the CHA 2 DS 2 -VASc scores are associated with the severity of coronary artery disease, its prognosis, and NRP in patients with acute MI, contrast-induced nephropathy after PPCI for acute coronary syndrome, in-stent restenosis, acute stent thrombosis, mechanical mitral valve thrombosis, and right ventricular dysfunction [8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 97%